Incidence of Orbital Exenteration: A Nationwide Study in France over the 2006-2017 Period. (4th March 2021) - Martel, A.; Nahon-Esteve, S; Gastaud, L.; Bertolotto, C.; Lassalle, S.; Baillif, S.; Charles, A.
ABSTRACT: Purpose: Orbital exenteration is a radical and disfiguring surgery mainly performed for treating orbital malignancies. Recently, several studies found favorable results in terms of overall survival with eye-sparing surgeries combined with targeted therapies and/or radiotherapy. The aim of this study was to assess the incidence of orbital exenteration and its evolution in France between 2006 and 2017. Methods: A national observational cohort study was conducted in France between January 2006 and December 2017. Data were collected from the national PMSI (Programme de Médicalisation des Systèmes d'Information) database provided by the CNAM (Caisse Nationale de l'Assurance Maladie). All patients undergoing orbital exenteration over the study period in France were included. Results: One thousand and fifty-seven patients were included. The mean annual number of orbital exenterations was 88.1 (63–117), corresponding to a mean incidence of 0.1/100, 000 inhabitants/year. A male predominance was noted (n = 626, 59.2%). Exenteration was mainly performed between 75 and 79 years. The underlying etiology was available for 821 patients (77.7%): malignancies were the most common (n = 755; 92.0%) followed by infectious diseases (n = 16; 1.9%). Over the study period, no statistical difference in the mean incidence of orbital exenteration was found ( p = .132). Conclusion: The mean annual incidence of orbital exenteration was 0.1/100, 000 inhabitants in France and was not significantly modified during the study period.